2018
DOI: 10.1103/physrevb.97.134422
|View full text |Cite
|
Sign up to set email alerts
|

Observation of end-vortex nucleation in individual ferromagnetic nanotubes

Abstract: The reversal of uniform axial magnetization in a ferromagnetic nanotube (FNT) has been predicted to occur through the nucleation and propagation of vortex domains forming at the ends. We provide experimental evidence for this behavior through dynamic cantilever magnetometry measurements of individual FNTs. In particular, we identify the nucleation of the vortex end domains as a function of applied magnetic field and show that they mark the onset of magnetization reversal. We find that the nucleation field depe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
(62 reference statements)
2
20
0
Order By: Relevance
“…For a certain range of γ's, the results of MC atomistic simulations have demonstrated that different reversal modes can occur along the hysteresis loop as a consequence of the high degree of metastability of the H states that facilitates different paths through the energy landscape when varying the magnetic field. In agreement with our results, recent experimental works on individual magnetic nanotubes 30,31 have also evidenced that short FeCoB nanotubes (0.6 µm long, 300 mn in diameter), with similar aspect ratios as the ones studied here, can be found in mixed states with end vortices of opposing or matching circulations depending on the magnetic history or experiment repetition. Moreover, the comparison of cantilever magnetometry 31 with micromagnetic simulations showed that reversal initiated with matching vortices is correlated to lower energies and smoother energy variations than for opposing vortices.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…For a certain range of γ's, the results of MC atomistic simulations have demonstrated that different reversal modes can occur along the hysteresis loop as a consequence of the high degree of metastability of the H states that facilitates different paths through the energy landscape when varying the magnetic field. In agreement with our results, recent experimental works on individual magnetic nanotubes 30,31 have also evidenced that short FeCoB nanotubes (0.6 µm long, 300 mn in diameter), with similar aspect ratios as the ones studied here, can be found in mixed states with end vortices of opposing or matching circulations depending on the magnetic history or experiment repetition. Moreover, the comparison of cantilever magnetometry 31 with micromagnetic simulations showed that reversal initiated with matching vortices is correlated to lower energies and smoother energy variations than for opposing vortices.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, the experimental study of Ref. 31 have already suggested that control over relative chirality can be achieved introducing structural asymmetries at the nanotube ends, but we have shown that this might be achieved also without modifying the tube structure.…”
Section: Discussionmentioning
confidence: 75%
“…where k i is the NW's spring constant and l e is its effective length [30,31]. We perform measurements of ∆f i (B) on several NWs by recording the thermal displacement PSD of their doublet modes as a function of B.…”
Section: Arxiv:181010865v1 [Cond-matmes-hall] 25 Oct 2018mentioning
confidence: 99%
“…[1][2][3][4] Yet unlike low-dimensional (0D, 1D, and 2D) nanostructures, 3D magnetic nanostructures are complex due to the presence of an extra degree of freedom for spins in their interactions. [5][6][7][8] Therefore, 3D magnetism investigation is a nontrivial matter. In addition, most conventional fabrication techniques, such as photolithography and electron beam lithography, face immense challenges to create 3D nanostructures due to resolution and alignment challenges.…”
Section: Introductionmentioning
confidence: 99%